THE CORRELATION BETWEEN ADENOID, TONSIL SIZE, AND BODY MASS INDEX WITH OBSTRUCTIVE SLEEP APNEA SEVERITY IN PEDIATRIC PATIENTS - Murdiyo, Mohammad Dwijo; Christianty, Finna; Leonard, Aditya (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Sleep disturbance in pediatrics produce daytime sleepiness and decrease productivity. Obstructive sleep apnea (OSA) was the most common cause of daytime sleepiness in children. Adenoid and tonsil hypertrophy was a major determinant of OSAS in pediatrics, in addition to other disorders such as craniofacial anomalies and obesity. Understanding the correlation between adenoid, tonsil size and body mass index (BMI) can be useful in managing optimal treatment strategies. Objective: To examine the correlation between adenoid, tonsil size, and BMI with OSA severity in pediatric patient with OSAS. Methods: The medical records of the Department of Otorhinolaryngology Head and Neck Surgery were utilised for this retrospective cross-sectional study spanning from January 1, 2016 to December 31, 2018. This research comprised a cohort of nineteen patients in total. The medical record was queried for the patient's age, sex, adenoid, and tonsil dimensions. The results of a pre-operative polysomnography to assess the severity of OSA were obtained as part of a routine examination and documented in the patient's medical records. Results: The correlation between variables showed in crosstabulation and Scatter Plot. A p-value below 0.05 indicated that the correlation coefficient of -0474 between adenoid size and OSA severity was statistically significant. The correlation between tonsil size and the severity of obstructive sleep apnea (OSA) was not statistically significant (R2 < 0.3, p < 0.05). Similarly, the correlation between BMI and OSA severity showed no significancy with p-value > 0.05, respectively. Conclusion: Adenoid size measured with Cohen and Konak ratio show significant correlation with OSA severity. While tonsil size and BMI showed no significancy in OSA severity.